2020
DOI: 10.48550/arxiv.2006.10194
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gender Inequality in Research Productivity During the COVID-19 Pandemic

Abstract: We study the disproportionate impact of the lockdown as a result of the COVID-19 outbreak on female and male academics' research productivity in social science. We collect data from the largest open-access preprint repository for social science on 41,858 research preprints in 18 disciplines produced by 76,832 authors across 25 countries in a span of two years. We find that during the 10 weeks after the lockdown in the United States, although the total research productivity increased by 35%, female academics' p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Pinho-Gomes et al (2020) observed this results in a disproportionate impact, especially on early career researchers. Vincent-Lamarre et al (2020) and Cui et al (2021) found the effect to be particularly pronounced at top-ranked research institutions.…”
Section: During the Pandemicmentioning
confidence: 95%
“…Pinho-Gomes et al (2020) observed this results in a disproportionate impact, especially on early career researchers. Vincent-Lamarre et al (2020) and Cui et al (2021) found the effect to be particularly pronounced at top-ranked research institutions.…”
Section: During the Pandemicmentioning
confidence: 95%
“…Schotte, Danquah, Osei, and Sen (2021) went as far as suggesting that the COVID-19 pandemic has the potential of accentuating existing inequalities. Studies have shown that the lockdown is entrenching traditional gendered inequalities (Arntz et al, 2020;Cui, Ding, & Zhu, 2020;King & Frederickson, 2021;Yildirim & Eslen-Ziya, 2021). In their study of the United States, Cui et al (2020) found that female academics' productivity dropped by 13.2 percent relative to that of male academics.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the lockdown is entrenching traditional gendered inequalities (Arntz et al, 2020;Cui, Ding, & Zhu, 2020;King & Frederickson, 2021;Yildirim & Eslen-Ziya, 2021). In their study of the United States, Cui et al (2020) found that female academics' productivity dropped by 13.2 percent relative to that of male academics. Eaton (2020) suggests the pandemic has disproportionately affected the productivity of early-career researchers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Etheridge et al (2020) find that, despite remaining constant during the pandemic, average WFH productivity declined for women Cui et al (2020). find that ten weeks after the lockdown in the United States, although the total research productivity (measured by published research preprints) increased by 35 percent, female academics' productivity dropped by 13.2 percent relative to that of male academics.7Rubin et al (2020) show that workplace restrictions and forced WFH saved commuting time, which lead to increased satisfaction among employees, especially among those who commuted by car.…”
mentioning
confidence: 99%